ADC quantification in basilar artery occlusion as an indicator of clinical outcome after endovascular treatment. Issue 6 (December 2017) - Pereira, Daniela; Fragata, Isabel; Amorim, José; Reis, João
Background: Acute ischemic stroke due to basilar artery occlusion (BAO) is associated with a dismal prognosis and, even though endovascular treatment (EVT) contributed to an improvement in clinical outcomes, patient selection is difficult and frequently results in futile recanalization. We investigated the prognostic value of baseline ADC quantification in patients with BAO undergoing EVT. Methods: We retrospectively evaluated MRI at admission in 11 patients with BAO undergoing EVT. Ischemic lesions were defined on baseline DWI and minimum ADC (minADC), ADC ratio and total area were quantified. Final infarction area was determined on follow-up T2WI/CT. We assessed the correlation between imaging parameters, recanalization grade and clinical scores (NIHSS at admission, NIHSS and mRS at discharge and mRS at three months) using Spearman rank correlation coefficient and correcting for multiple comparisons with the false discovery rate (FDR). Results: Lower values of minADC at admission MRI are strongly correlated with higher scores in NIHSS (rs  = −0.845, p  = 0.001) and mRS at discharge (rs  = −0.743, p  = 0.009). We also found a negative correlation between minADC and NIHSS at admission (rs  = −0.67, p  = 0.02), mRS at three months and difference between pre- and post-treatment ischemic area (rs  = −0.664, p  = 0.026) that lost significance with FDR correction. Ischemic area and TICI grade were not significantly associated with clinical results. Conclusions: ADC quantification of ischemic lesions at baseline MRI seems to predict clinical outcome in patients with BAO undergoing EVT, more importantly than ischemic area or TICI grade.